(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, national in the process of inter-ethnic relations in Uzbekistan information about the importance of cultural centers, the role of state policy in the formation of national harmony, the processes of inter-ethnic tolerance in Uzbekistan.